Uzbekistan State World Languages University - Yusupov Shaxboz; DSc. Paluanova X.D (Periodica Journal, 2022)
The article deals with the importance of active verbs in two languages, English and Uzbek. Its sentimentality is public by many. In reply, approximately instructors and linguists are reconsidering the way language is investigated and compared for extended admission.
Keywords: semantics; generative syntax; Aspectual semantics